Racial Extractivism: Neoliberal White Settler Colonialism and Tar Sands Extraction - Preston, Jennifer Lauren (York University, 2017)
This dissertation traces the reoccurrence of logics which attempt to justify white settler occupation and the extraction, theft and harm of Indigenous lands and life in the Athabasca region and in relation to the extraction, transportation and marketing of bitumen. By tracing the entrenchment of notions of white entitlement to land and life in this context, the repetitiveness of normalized epistemic and ontological colonial violence comes into view as just as much a part of the contemporary neoliberal moment as it was during the founding of the nation-state. The Athabasca region is home to the worlds second largest deposit of oil and is being aggressively extracted despite being an unconventional oil source that requires massive amounts of energy, water, toxic chemicals and irreversible environmental damage to extract. Herein, historical narratives of empire and nation-building are examined and linked to extractive industries over time, first within a colonial mercantilist economy, then within a capitalist economic structure and finally within the contemporary neoliberal context. The relationships between private capital and the white settler government are explored as deeply interconnected and as mutually involved in the creation and maintenance of normalized white settler colonialism. Furthermore, the dissertation examines the extractive practices of white settler colonialism as always already informed by logics of white supremacy, and develops the concept of racial extractivism as a theoretical lens through which race, racism and racialization as well as colonialism may be centered in studies of resource extraction and nation-state building. Influenced by Cedric Robinsons (1983) theorization of racial capitalism, racial extractivism contributes to studies of political economy, settler colonialism, and to cultural studies and is utilized in analyzing the more regionally specific context of tar sands extraction and the contemporary discursive strategies supporting it and marketing it domestically and internationally. Lastly, the project examines neoliberalism and the securitization of the industry and attempts to think about racial extractivism intersectionally, as white settler state power combines with the forces of private oil and gas companies to discursively and affectively normalize ongoing colonial violence.